An efficient EYDFA with a 54 dB small signal gain - Muhd-Yassin, Shahrin Zen; Harun, Sulaiman Wadi; Abdul-Rashid, Hairul Azhar; Abd-Rahman, Mohd Kamil; Rahman, Faidz Abd; Ahmad, Harith (John Wiley & Sons, 2007)
An efficient erbium/ytterbium codoped fiber amplifier is demonstrated by using a dual-stage configuration with a midway optical isolator and a band-pass filter (BPF). The amplifier achieved a maximum low signal gain of 54 dB and a corresponding noise figure of 6.5 dB (1536 nm) using the input signal power and total pump power of -50 dBm and 140 mW. respectively. The gain obtained by the amplifier was about 12.5 dB higher than the gain of a conventional single-stage amplifier whereas its noise figure was 3.5 dB lower. Both isolator and BPF contribute to gain and noise figure improvements by blocking backward and forward propagating amplified spontaneous emission.